Impact of SO2 on elemental mercury oxidation over CeO2–TiO2 catalyst - Li, Hailong; Wu, Chang-Yu; Li, Ying; Li, Liqing; Zhao, Yongchun; Zhang, Junying (Chemical engineering journal (Lausanne, Switzerland : 1996), 2013)
[Display omitted] ► SO2 exhibited different, even contrary, effects on Hg0 oxidation in different conditions. ► With O2, few SO2 promoted Hg0 oxidation, while excess SO2 inhibited Hg0 oxidation. ► There is a balance SO2 concentration, where no obvious effect of SO2 can be observed. ► NO catalyzed SO2 conversion to SO3, and thus relieved the inhibitive effect of SO2. Effect of SO2 on elemental mercury (Hg0) oxidation over a highly active CeO2–TiO2 catalyst was systematically investigated. SO2 was found to have different, even contrary, effects on Hg0 oxidation under different flue gas conditions. In pure N2 atmosphere, SO2 inhibited Hg0 oxidation. In N2 plus O2 atmosphere, low concentration of SO2 promoted Hg0 oxidation, while high concentration of SO2 deteriorated Hg0 oxidation. The promotional effect of SO2 on Hg0 oxidation was probably due to SO3 generated from SO2 oxidation, and the inhibitive effect of SO2 on Hg0 oxidation was attributed to the competitive adsorption between SO2 and Hg0. The results suggest a balance point for SO2 concentration, where the promotional effect on Hg0 oxidation by SO3 originated from SO2 is equal to the inhibitive effect of SO2 on Hg0 adsorption and subsequent oxidation via the Langmuir–Hinshelwood mechanism. In the presence of NO, SO2 with the aid of O2 exhibited promotional effect on Hg0 oxidation through NO-catalyzed oxidation to form SO3 and hence a balance point of higher SO2 concentration. However, without O2, SO2 greatly limited Hg0 oxidation in the presence of NO. When HCl was present, most Hg0 oxidation was due to reactions between active chlorine species and adsorbed Hg0. SO2 inhibited Hg0 adsorption and therefore deteriorated Hg0 oxidation by chlorine species. When both NO and HCl were present, NO accelerated the conversion of SO2 to SO3, and hence relieved the prohibitive effect of SO2 on Hg0 oxidation by HCl.